Glaciological Data Collected by the 43rd Japanese Antarctic Research Expedition during 2001-2003 - Saito, Takashi; Kinoshita, Jun; Kanehama, Shin; Yoshii, Koji; Kamiyama, Kokichi (National Institute of Polar Research, 2007)
P(論文) departmental bulletin paper